Magnetic, thermal and spectral behaviour of 3-chloro-2-nitrobenzoates of Co(II), Ni(II), and Cu(II) - Ferenc, Wieslawa; Cristóvão, Beata; Sarzyński, Jan; Paszkowska, Barbara (Eclética Química, 2006)
Physico-chemical properties of 3-chloro-2-nitrobenzoates of Co(II), Ni(II) and Cu(II) were synthesized and studied. The complexes were obtained as mono- and dihydrates with a metal ion to ligand ratio of 1 : 2. All analysed 3-chloro-2-nitrobenzoates are polycrystalline compounds with colours depending on the central ions: pink for Co(II), green for Ni(II) and blue for Cu(II) complexes. Their thermal decomposition was studied in the range of 293 – 523 K, because it was found that on heating in air above 523 K 3-chloro-2-nitrobenzoates decompose explosively. Hydrated complexes lose crystallization water molecules in one step and anhydrous compounds are formed. The final products of their decomposition are the oxides of the respective transition metals. From the results it appears that during dehydration process no transformation of nitro group to nitrite takes place. The solubilities of analysed complexes in water at 293 K are of the order of 10 -4 – 10 -2 mol / dm 3 .